2020
DOI: 10.12997/jla.2020.9.2.291
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Expression of the Serine Palmitoyltransferase Subunit Sptlc2 Reduces Lipid Droplets in the Liver by Activating VLDL Secretion

Abstract: Objective: Ceramide is a signaling molecule that contributes to insulin resistance and hepatosteatosis. In the present study, we activated de novo ceramide synthesis by inducing the hepatic expression of Sptlc2 to investigate the role of ceramide in glucose and lipid metabolism. Methods: We first constructed an adenovirus containing Sptlc2 (AdSptlc2), which encodes a major catalytic subunit of serine palmitoyltransferase (SPT). We then infected hepatocytes and mice fed a regular diet with AdSptlc2 to activate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…It has been demonstrated that the adenoviral expression of Sptlc2 increases ceramide levels in vitro, activating the stress-activated c-Jun N-terminal kinase (JNK) inhibiting insulin signal. However, the same paper indicated that SPTLC2 increased insulin sensitivity in vivo [ 53 ], suggesting that a subtle protective mechanism could be activated in C to maintain glucose homeostasis through the activation of SPTLC2 . Further investigations are ongoing to clarify this issue.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the adenoviral expression of Sptlc2 increases ceramide levels in vitro, activating the stress-activated c-Jun N-terminal kinase (JNK) inhibiting insulin signal. However, the same paper indicated that SPTLC2 increased insulin sensitivity in vivo [ 53 ], suggesting that a subtle protective mechanism could be activated in C to maintain glucose homeostasis through the activation of SPTLC2 . Further investigations are ongoing to clarify this issue.…”
Section: Discussionmentioning
confidence: 99%
“…In the lipid research field, various pathways involved in lipid metabolism or lipidomic analysis in pre-pathological and pathological conditions such as obesity, metabolic syndrome, diabetes, and NAFLD have been actively studied. 5 24 25 26 The newly established intravital imaging methods of LDs in in vivo physiological and pathological microenvironments demonstrated in our study will provide a highly useful tool for future investigations to explore novel molecular and cellular mechanisms involving lipid in physiological and various pathological conditions or to assess novel treatment strategies to alleviate deposition of lipids in preclinical animal models.…”
Section: Discussionmentioning
confidence: 91%
“…SPT catalyses the rate-limiting step in the de novo ceramide biosynthesis pathway. In mice with adenovirus-induced overexpression of the Sptlc2 gene in the liver, hepatic ceramide was found to modulate hepatosteatosis and the insulin response via increased VLDL secretion and inhibition of gluconeogenesis in vivo [ 35 ].…”
Section: Discussionmentioning
confidence: 99%